ANALISIS JARINGAN KOMUNIKASI MASYARAKAT DALAM KESIAPAN MENGHADAPI BENCANA LONGSOR DI KAKI GUNUNG BURANGRANG KAB. BANDUNG BARAT - Ditha Prasanti; Ikhsan Fuady (Universitas Gadjah Mada, 2018)
West Bandung Regency is an area that has hilly topography and mountains. It causes the area of West Bandung to be prone to landslides. One way that can be done to reduce the risk of landslide disaster is to improve the effective communication network. This study aims to describe and analyze the community communication network In Landslide Preparedness Facing Landslide at Burangrang Mountain Foot Kab. West Bandung. This research method use approach of communication network analysis using Ucinet 6.0. The results showed that the structure of risk communication network network is personalized interlocking (interlocking personal network). The average value of local centrality on this network is 4.113. Based on the results of the analysis that has been done, there are several clicks in the communication network; some actors who act as star in the network; some isolate individuals who do not get or relate to other parties to obtain information related to landslide disaster.